Analisis Penolakan dan Pengulangan Citra Radiografi pada Modalitas Computed Radiography AGFA CR 35-X di Instalasi Radiologi RSUD DR. R. Goeteng Taroenadibrata Purbalingga - Ikko Justian Fajarrissetyo; Panji Wibowo Nurcahyo; Asri Indah Aryani (Poltekkes Kemenkes Semarang, 2015)
Background: Reject film analysis program is a systematical process to count repeated images and determine the cause of the repeat, so it could be minimalized or banished even. This research aims to find out the reject percentage, cause of each reject percentage and the efforts to reduce it.Method: This research was a quantitative model with descriptive approach. The research has been done in February, April and May of 2016. Data were obtained from observation, documentation and interview with three radiographers. Data was analyzed by Paretto’s diagram to identify the influence of each cause.Results: In February, April and May by orders the percentage of the radiographic images reject and repeat are 4,86%, 4,65%, 6,95%. The factors of digital images reject and repeat were patient’s position (1,65%, 1,05%, 0,84%), uncorrect exposure value (1,30%, 0,98%, 1,87%), miscellaneous reasons (0,35%, 0,38%, 0,28%), too narrow collimation (0,26%, 0,68%, 0,47%), unsharpness (0,17%, 0,0%, 0,0%), digiscan fault (0,09%, 0,30%, 0,84%) and x-ray equipment’s fault (0,09%, 0,38%, 0,65%). Meanwhile in radiographic film factor, unwanted film (0,61%, 0,30%, 0,67%), printer’s fault (0,35%, 0,08%, 0,95%), patient’s position (0,0%, 0,23%, 0,0%), miscellaneous reasons (0,0%, 0,23%, 0,19%), too narrow collimation (0,0%, 0,0%, 0,90%) and unsharpness (0,0%, 0,08%, 0,0%).Conclusion: The efforts to reduce radiographic images reject and repeat were applying effective communications with patients and their family and taking notes whenever a failure occurs